Molecular Photoacoustic Imaging of Follicular Thyroid Carcinoma - Levi, Jelena; Kothapalli, Sri-Rajashekar; Bohndiek, Sarah; Yoon, Joon-Kee; Dragulescu-Andrasi, Anca; Nielsen, Carsten; Tisma, Aleksandra; Bodapati, Sunil; Gowrishankar, Gayatri; Yan, Xinrui; Chan, Carmel; Starcevic, Daniela; et al. (Clinical cancer research, 2013)
Purpose: To evaluate the potential of targeted photoacoustic imaging as a noninvasive method for detection of follicular thyroid carcinoma. Experimental Design: We determined the presence and activity of two members of matrix metalloproteinase family (MMP), MMP-2 and MMP-9, suggested as biomarkers for malignant thyroid lesions, in FTC133 thyroid tumors subcutaneously implanted in nude mice. The imaging agent used to visualize tumors was MMP-activatable photoacoustic probe, Alexa750-CXeeeeXPLGLAGrrrrrXK-BHQ3. Cleavage of the MMP-activatable agent was imaged after intratumoral and intravenous injections in living mice optically, observing the increase in Alexa750 fluorescence, and photoacoustically, using a dual-wavelength imaging method. Results: Active forms of both MMP-2 and MMP-9 enzymes were found in FTC133 tumor homogenates, with MMP-9 detected in greater amounts. The molecular imaging agent was determined to be activated by both enzymes in vitro, with MMP-9 being more efficient in this regard. Both optical and photoacoustic imaging showed significantly higher signal in tumors of mice injected with the active agent than in tumors injected with the control, nonactivatable, agent. Conclusions: With the combination of high spatial resolution and signal specificity, targeted photoacoustic imaging holds great promise as a noninvasive method for early diagnosis of follicular thyroid carcinomas. Clin Cancer Res; 19(6); 1494–502. ©2013 AACR.